Angiogenesis and Inflammation Crosstalk in Diabetic Retinopathy. Issue 11 (21st July 2016) - Capitão, Margarida; Soares, Raquel
ABSTRACT: Diabetic retinopathy (DR) is one of the most prevalent microvascular complications of diabetes and one of the most frequent causes of blindness in active age. Etiopathogenesis behind this important complication is related to several biochemical, hemodynamic and endocrine mechanisms with a preponderant initial role assumed by polyol pathways, increment of growth factors, accumulation of advanced glycation end products (AGE), activation of protein kinase C (PKC), activation of the renin‐angiotensin‐aldosterone system (RAAS), and leukostasis. Chronic and sustained hyperglycemia works as a trigger to the early alterations that culminate in vascular dysfunction. Hypoxia also plays an essential role in disease progression with promotion of neovascularization and vascular dystrophies with vitreous hemorrhages induction. Thus, the accumulation of fluids and protein exudates in ocular cavities leads to an opacity augmentation of the cornea that associated to neurodegeneration results in vision loss, being this a devastating characteristic of the disease final stage. During disease progression, inflammatory molecules are produced and angiogenesis occur. Furthermore, VEGF is overexpressed by the maintained hyperglycemic environment and up‐regulated by tissue hypoxia. Also pro‐inflammatory mediators regulated by cytokines, such as tumor necrosis factor (TNF‐α) and interleukin‐1 beta (IL‐1β), and growth factors leads to the progression of these processes, culminating in vasopermeability (diabetes macular edema) and/or pathological angiogenesis (proliferative diabetic retinopathy). It was found a mutual contribution between inflammation and angiogenesis along the process. J. Cell. Biochem. 117: 2443–2453, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Diabetic retinopathy is a frequent cause of blindness, and one of the major morbidities in diabetes. The interplay between inflammation and angigoenesis is established. Anti‐VEGF intravitreal therapy controls the progression of disease but does not prevent loss of visual acuity. An overview of the molecular mechanisms involved, biochemical parameters, and therapeutic targets is provided.